Assessment of Satisfaction Level of Residents in a Housing Community, A Case of City Paradise, Lalitpur - Pathak, Nistha; Bajracharya, Ashim Ratna (Journal of Engineering Technology and Planning, 2022)
As mentioned by Canter and Rees (1982), residential satisfaction (RS) is the degree to which the residential environment helps dwellers achieve their goals, and it evaluates the extent to which the current housing environment is meeting residents’ needs, expectations and ambitions. Residential satisfaction in planned housing is a widely researched topic in global context, however, in case of Nepal, not much research has been done on the topic. There are many planned housing communities being developed, but the living experience of the residents are rarely studied, and neither their perception in living in gated communities. This paper aims to contribute to theory and practice concerning residential satisfaction in housing community of Lalitpur known as City Paradise which is one of the major projects of Civil Homes Housing Company. This study is based in a household survey conducted in City Paradise Housing community. Data was collected from 40 households out of total 72 units, through simple random sampling to avoid any kind of biasness during the study. Data was analyzed to study the level of satisfaction, using Likert scale, among the residents with respect to design and planning characteristics of housing units, public facilities and services, and neighborhood. The results of analysis show that the respondents comparatively had higher satisfaction levels in context of neighborhood planning and less satisfied with design and planning features of housing and provision of public facility and convenience. Residents are quite satisfied with the child-friendly environment in their neighborhood, but planning and layout of buildings are not good enough to meet their satisfaction level. This research helps to address current issues related to satisfaction level of the residents of housing community and recommend the possible ways for its betterment.